Identification of conditions for ultrasonic effect on gas-dispersed medium and creation of radiators to increase the efficiency of coagulation in devices with swirling flow - Vladimir N. Khmelev; Viktor A. Nesterov; Andrey V. Shalunov; Sergey A. Terentyev (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The presence and uncontrolled distribution of aerosols of various substances in the air, which have a negative impact on humans, flora and fauna. This problem is especially acute in the extraction, processing and combustion of georesources. The most effective way to solve the problem is the use of high-intensity ultrasonic vibrations, the effect of which on aerosols causes convergence and agglomeration of small particles into large ones. However, at low concentrations, the particle coagulation efficiency is not sufficient to increase the recovery rate of gas treatment equipment. Therefore, there is a need to find new ways to optimize ultrasonic equipment for coagulation of fine particles in order to increase its efficiency. Aim. To determine the optimal conditions for ultrasonic influence on a swirling gas-dispersed flow, ensuring maximum efficiency of agglomeration of highly dispersed particles. Carrying out comparative studies of coagulation of particles when exposed to ultrasonic fields generated by different types of radiators and their combined effects will make it possible to determine the effectiveness of ultrasonic coagulation and the optimal design scheme of ultrasonic exposure. Objects. Coagulation of particles under ultrasonic impact, formed by various types of radiators. Methods. Computer modeling of the generated ultrasonic field using the finite element method using harmonic acoustic analysis. Finite element modeling and design of disk radiators using modal analysis. To determine the characteristics of the aerosol, a Malvern Spraytec Particle Analyzer was used. Results. The results of calculations and experiments have shown that the use of an extended ultrasonic tubular radiator operating on a bending-diametric mode of vibration and forming a ring standing wave with a sound pressure level of 162–165 dB as the main source of ultrasonic impact for devices with swirling flows may be the most energy efficient. Further increase in the efficiency of coagulation can only be achieved by the combined action of a tubular radiator and a longitudinally oscillating radiator. This significantly modifies the field structure and provides not only an increase in the sound pressure level (up to 167 dB), but also in the number of formed nodal surfaces (up to 44).